Peran Hukum dan Pembangunan Ekonomi Indonesia (Tinjauan Terhadap Aspek Penanaman Modal Asing) - Wencislaus Sirjon Nansi (Universitas Atma jaya Makassar, 2011)
The Presence of Economic opportunities, political stability and legal certainty are important in order for foreign capital can enter a country; and the aspect of legal certainty is the key word which is the main consideration of foreign investors. any change made in the regulation of foreign investment in Indonesia, is one of the goverment's efforts to create an open and conducive climate for foreign investments, overseeing the contruction of national unity, which ultimately aims for the walfare of the people of Indonesia.